Effect of exercise intervention on health-related quality of life in middle-aged and older people with osteoporosis: a systematic review and meta-analysis - Di Geng; Xiaogang Li; Yan Shi (PeerJ)
Background Osteoporosis is a common condition affecting middle-aged and older people, posing a serious threat to their health-related quality of life (HRQOL). In recent years, multiple studies have investigated the impact of exercise interventions on HRQOL in middle-aged and older individuals with osteoporosis, but the conclusions have been inconsistent. The aim of this study was to determine the true significance of exercise interventions on HRQOL in middle-aged and older individuals with osteoporosis and to identify optimal exercise prescriptions. Methods Six databases were searched for RCTs on the impact of exercise interventions on HRQOL in middle-aged and older individuals with osteoporosis. The methodological quality of the study was evaluated with Cochrane risk assessment tool. The effect size pooling, heterogeneity testing, and publication bias were analyzed using Review Manager 5.4 software. Result A total of 14 RCTs involving 1,214 participants were included, published between 2007 and 2022. The pooled results demonstrated that exercise interventions significantly improved general HRQOL (SMD = 0.79, 95% CI [0.34–1.24], p = 0.0006). In terms of physical HRQOL, significant improvements were observed in bodily pain (SMD = 0.51, 95% CI [0.24–0.78], p= 0.0002), physical function (SMD = 0.56, 95% CI [0.21–0.91], p = 0.002), role physical (SMD = 0.39, 95% CI [0.14–0.64], p = 0.003), and general health (SMD = 0.68, 95% CI [0.25–1.11], p = 0.002). Regarding mental HRQOL, significant improvements were found in vitality (SMD = 0.58, 95% CI [0.15–1.01], p = 0.008), social function (SMD = 0.37, 95% CI [0.17–0.58], p = 0.0004), and mental health (SMD = 0.50, 95% CI [0.25–0.74], p < 0.0001). Subgroup analysis results indicated that resistance training (SMD = 1.01, 95% CI [0.50–1.52], p = 0.0001), intervention frequency of at least three times per week (SMD = 0.80, 95% CI [0.22–1.38], p = 0.007), and intervention duration of 13–24 weeks (SMD = 0.85, 95% CI [0.37–1.33], p = 0.0005) had large and significant effects on general HRQOL improvements. Conclusion Exercise interventions improved HRQOL in middle-aged and older individuals with osteoporosis. Resistance training has shown greater benefits than mixed exercises. The optimal frequency is at least three per week, yielding the greatest improvement. Exercise interventions lasting 13–24 weeks had the most pronounced effect compared to other durations. Registration PROSPERO (No. CRD42023438771).